2018
DOI: 10.1016/j.tracli.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human dendritic cell subsets for immune tolerance induction

Abstract: To cite this version:N. Deluce-Kakwata-Nkor, L. Lamendour, V. Chabot, A. Héraud, Z. Ivanovic, et al.. Differentiation of human dendritic cell subsets for immune tolerance induction. Transfusion Clinique et Biologique, Elsevier, 2018, 25 (1), pp.90-95. 10.1016/j.tracli.2017 Please cite this article in press as: Deluce-Kakwata-nkor N, et al. AbstractObjectives. -Since no further progress was achieved, in order to improve the long-term organ transplantation outcome, the immune tolerance appears as an interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…T regs are induced by DCs, which are antigen-presenting cells with critical roles in the induction and regulation of immunity [25]. In particular, BDCA2 + and BDCA4 + pDCs exert tolerogenic functions when mediating T reg development and increasing T reg frequencies [26,27]. Our data showed that the percentages of mDC and pDC subsets and MFI analysis of BDCA1-4 did not differ between mTORI-and CNI-treated patients.…”
Section: Discussionmentioning
confidence: 60%
“…T regs are induced by DCs, which are antigen-presenting cells with critical roles in the induction and regulation of immunity [25]. In particular, BDCA2 + and BDCA4 + pDCs exert tolerogenic functions when mediating T reg development and increasing T reg frequencies [26,27]. Our data showed that the percentages of mDC and pDC subsets and MFI analysis of BDCA1-4 did not differ between mTORI-and CNI-treated patients.…”
Section: Discussionmentioning
confidence: 60%
“…Likewise, differentiation of immunosuppressive DC-SIGN+ DCs in prostate cancer tissue was orchestrated primarily by factors derived from adjacent stroma [ 40 ]. After stimulation with LPS, DC-SIGN+ DCs were shown to dramatically increase the secretion of pro-tolerant cytokine IL-10 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, immature DCs act as sentinels against invading pathogens and as tissue scavengers, capturing apoptotic and necrotic cells [57]. Accordingly, immature DCs are essential for inducing and maintaining immune tolerance [58]. DCs internalize cell apoptosis and the loss of critical details in polyps, such as tissue turnover.…”
Section: The Role Of Gut Microbiota In Dysbiosis and Crcmentioning
confidence: 99%